HUBUNGAN SELF-EFFICACY TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMK PADA MATERI BARISAN DAN DERET ARITMATIKA - Abdul Robbi Misbahudin (Journal on Education, 2019)
This research aims to determine the relationship between students' self-efficacy on critical thinking skills of vocational students in arithmetic sequence and series material. The method used is quantitative by correlation method. This research was conducted in one of the Vocational Schools in Cimahi City with a population of all students of class XI and a sample of class XI-RPL 5 of 30 people. The instrument used in this study was a questionnaire instrument to measure students 'level of self-efficacy and test instruments to measure students' critical thinking skills. The results of the analysis show that there is a significant relationship between students 'self-efficacy with students' mathematical critical thinking abilities and the effect of self-efficacy on the critical thinking skills of students of Vocational High School class XI which is 19.89% while the remaining 80.11% is influenced by other factors